2006
DOI: 10.1189/jlb.0805484
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dendritic cell function in Crohn’s disease patients with NOD2 3020insC mutation

Abstract: The nucleotide oligomerization domain 2 (NOD2) 3020insC (NOD2fs) mutation increases susceptibility to Crohn's disease (CD), but the mechanism remains controversial. Loss-of-function and gain-of-function phenotypes have been described as a result of NOD2fs. Here, we show that dendritic cells (DC) derived from CD patients homozygous for this mutation respond normally to purified Toll-like receptor (TLR) ligands but fail to up-regulate the costimulatory molecules CD80 and CD86 in response to the NOD2 ligand muram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…However, a recent study utilizing mice with the same gene knocked in demonstrated a lossof-function phenotype with reduced levels of cytokine in response to MDP and bacterial infection (61). These later findings concur with studies utilizing cells from CD patients, suggesting a loss-offunction mutation (15,16,(62)(63)(64)(65). When the response of cells from CD patients bearing NOD2 mutations was compared with cells with WT NOD2, the potentiation of cytokine response by MDP was lost in patients with mutated NOD2 (14)(15)(16).…”
Section: Discussionsupporting
confidence: 52%
“…However, a recent study utilizing mice with the same gene knocked in demonstrated a lossof-function phenotype with reduced levels of cytokine in response to MDP and bacterial infection (61). These later findings concur with studies utilizing cells from CD patients, suggesting a loss-offunction mutation (15,16,(62)(63)(64)(65). When the response of cells from CD patients bearing NOD2 mutations was compared with cells with WT NOD2, the potentiation of cytokine response by MDP was lost in patients with mutated NOD2 (14)(15)(16).…”
Section: Discussionsupporting
confidence: 52%
“…Each of the three CD polymorphisms are located within or near the leucine rich repeat, sensing domain of Nod2, and each results in a decreased capacity to activate NF-κB in response peptidoglycan or MDP stimulation [39,[44][45][46][47][48] . The frameshift mutation, Leu1007fsinsC demonstrates a largely complete deficiency in the capacity to signal in response to MDP stimulation [45] .…”
Section: Nod2 (Card15) Associations To Ileal CDmentioning
confidence: 99%
“…As each of the three major mutations demonstrates decreased function in primary human cells [39,[44][45][46][47][48] , Nod2-deficient murine models provide an important model for human disease. The absence of intestinal inflammation in Nod2-deficient mice further highlights the insufficiency of this pathway alone to induce CD [42,53] .…”
Section: Nod2 (Card15) Associations To Ileal CDmentioning
confidence: 99%
“…The second model involves altered TLR2 signaling, proposing an inhibitory role of Nod2 in the TLR2-mediated Th1 responses (17). However, other groups have shown that TLR2 responses are normal in different lines of Nod2-deficient mice, and there may be a synergistic rather than a negative effect on TLR2 stimulation in human and mouse cells (10,(18)(19)(20)(21). The third model proposes that mutations in NOD2 may result in altered mucosal host-microbe interactions (13).…”
mentioning
confidence: 99%